Reflexive Account of an Indonesian International Student’s Challenges and Opportunities in a U.K. University’s Doctoral Education Program - Samanhudi, Udi (Journal of International Students, 2021)
This study is an autoethnography focused on providing an in-depth understanding of my personal experiences as an international doctoral student from Indonesia in a university in the United Kingdom. In this article, I share and discuss some challenging situations during my doctoral study particularly in writing a 5,000-word-essay for nine modules, which required me to explicitly perform critical thinking in my writing. I found that expressing my critical voice in writing was not easy, especially at the outset of my doctoral study period. I believe my previous education experiences neglected critical thinking pedagogy in the classroom, which is one of the most important factors causing this kind of difficulty of demonstrating critical thinking especially in writing.